Absaroka Valley [large type] - Paine, Lauran (Circle V western., 2019)
"Samuel Parker is traveling through the mountains hoping to find a place to settle his two children before lung fever kills him when they help an injured man whom Samuel fears may be an outlaw. As the man heals, he directs Samuel to Absaroka Valley where they are drawn into the center of a land fight"--